2016
DOI: 10.1002/anie.201510308
|View full text |Cite
|
Sign up to set email alerts
|

A Sugar‐Based Gelator for Marine Oil‐Spill Recovery

Abstract: Marine oil spills constitute an environmental disaster with severe adverse effects on the economy and ecosystem. Phase-selective organogelators (PSOGs), molecules that can congeal oil selectively from oil-water mixtures, have been proposed to be useful for oil-spill recovery. However, a major drawback lies in the mode of application of the PSOG to an oil spill spread over a large area. The proposed method of using carrier solvents is impractical for various reasons. Direct application of the PSOG as a solid, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
97
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 140 publications
(100 citation statements)
references
References 38 publications
1
97
0
Order By: Relevance
“…[1][2][3][4][5][6][7] To address this issue, we need more effective methods of collecting and recovering insoluble oils ando rganics olvents from polluted water.R esearchers have developed numerous products and approaches forw ater purification, such as oil-containment booms, [8][9][10] absorbent compounds, [11][12][13] and variouso il/water separation techniques, [14][15][16][17] particularly those that are based on materialw ettability.F or example, severals uperhydrophobic/superoleophilic materials, including polyester-based compounds, [18,19] surfacemodified metal meshes, [20,21] and textiles, [22,23] have shown sat-isfactoryp erformancei ni solating oils that have ah igher density than water. [1][2][3][4][5][6][7] To address this issue, we need more effective methods of collecting and recovering insoluble oils ando rganics olvents from polluted water.R esearchers have developed numerous products and approaches forw ater purification, such as oil-containment booms, [8][9][10] absorbent compounds, [11][12][13] and variouso il/water separation techniques, [14][15][16][17] particularly those that are based on materialw ettability.F or example, severals uperhydrophobic/superoleophilic materials, including polyester-bas...…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6][7] To address this issue, we need more effective methods of collecting and recovering insoluble oils ando rganics olvents from polluted water.R esearchers have developed numerous products and approaches forw ater purification, such as oil-containment booms, [8][9][10] absorbent compounds, [11][12][13] and variouso il/water separation techniques, [14][15][16][17] particularly those that are based on materialw ettability.F or example, severals uperhydrophobic/superoleophilic materials, including polyester-based compounds, [18,19] surfacemodified metal meshes, [20,21] and textiles, [22,23] have shown sat-isfactoryp erformancei ni solating oils that have ah igher density than water. [1][2][3][4][5][6][7] To address this issue, we need more effective methods of collecting and recovering insoluble oils ando rganics olvents from polluted water.R esearchers have developed numerous products and approaches forw ater purification, such as oil-containment booms, [8][9][10] absorbent compounds, [11][12][13] and variouso il/water separation techniques, [14][15][16][17] particularly those that are based on materialw ettability.F or example, severals uperhydrophobic/superoleophilic materials, including polyester-bas...…”
mentioning
confidence: 99%
“…Subsequently, a piece of SMF was placed at the oil/water interface and it was observed that the SMF selectively absorbed the oil phase without any traces of water, even after direct exposure to the aqueous phase as shown in Figure A–D and Movie 2. The absorbed oil was re‐collected separately (Figure D) by simple manually squeezing process, in comparison to refluxing and burning process . However, when the uncoated MF was placed at the oil/water interface, it absorbed the water and hence, remained inept to absorb the oil as shown in Figure S3 and Movie 3.…”
Section: Resultsmentioning
confidence: 99%
“…The strategic modification of commercially available spongy substrates with essential physical and chemical parameters that conferred superhydrophobicity, has recently been utilized for developing reusable and selective oil‐absorbents. Moreover, the high compressibility provided a facile basis for energy‐efficient and environment friendly removal of the absorbed oil, compared to the other existing approaches‐such as refluxing, burning etc . The low density (≈10 mg cm −3 ), high porosity (average pore size of 150±5 μm) of melamine foam inherently allowed greater absorption of the oily phase, selectively, after embedding the selected spongy substrate with artificial superhydrophobicity .…”
Section: Introductionmentioning
confidence: 99%
“…Whereas the former imparts conformational rigidity and amphiphilicity to otherwise hydrophilic sugar molecules, the latter provides the supramolecular glue for self‐assembly in the form of hydrogen bonding. The anomeric substituents do not alter the gelation ability much . Thus, we planned to synthesize a library of gelators through copper‐catalyzed azide–alkyne cycloaddition (click reaction) of a sugar gelator having an anomeric azide with various alkynes.…”
Section: Introductionmentioning
confidence: 99%